Acute-phase serum superoxide dismutase level as a predictive biomarker for stroke-associated infection. (1st February 2020) - Lin, Shao-Peng; Tu, Chuanmeizi; Huang, Wenyao; Wu, Yi; Lin, Pei-Yi; Ye, Shan; Long, Youming; Xu, Weiqiang; Chen, Shishi; Wen, Yong-Shuai; Ou, Yongqi; Li, Xiujin; et al.
Abstract: Background and Purpose : Oxidative stress is involved in the development of infections. However, whether oxidative stress indicators can be used as markers of stroke-associated infection (SAI) is still unclear. The purpose of this study was to test the predictive values of superoxide dismutase (SOD) and malondialdehyde (MDA) levels for SAI incidence. Methods : A total of 45 consecutive patients with ischemic stroke who were admitted to our hospital were enrolled. A prospective study was carried out to observe the occurrence of SAI during the first 7 days after stroke. Accordingly, the patients were divided into SAI and non-SAI groups. The relationship between SOD and MDA serum levels and SAI was analyzed. Results : The patients in the SAI group had significantly higher serum SOD levels than those in the non-SAI group (41.638 ± 3.428 U/ml vs. 36.542 ± 9.114 U/ml, p = 0.033). However, there were no significant differences in MDA levels between the SAI and non-SAI group ( p > 0.05). The discriminating ability of serum SOD level for SAI was measured using an ROC curve. Serum level of SOD >38.16 U/ml was useful in diagnosing SAI with a sensitivity of 88% and a specificity of 61%. Kaplan-Meier curves showed that the group with serum SOD level >38.16 U/ml had higher rates of SAI incidence ( χ 2 = 9.688, p = 0.002; log rank test). Furthermore, Cox regression analysis indicated that a serum SOD level >38.16 U/ml was an independent risk factor for SAI (hazard ratio = 5.836; 95% CI, 1.298–26.244; p = 0.021). Conclusions : Acute-phase serum SOD level could be a predictor of SAI.